2017
DOI: 10.1039/c7ra05343f
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of microporous carbon spheres from high amylose pea maltodextrin

Abstract: Porous carbon materials have attracted great interest for their many industrial applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 34 publications
(30 reference statements)
0
12
0
Order By: Relevance
“…Due to the capacity of including some FR components of low molecular weight in their cavities, BCD and BCD derivatives reduce the release to the environment of these species, resulting in an increase fire retardance activity and in more environmental friendly behavior. Introduction in FR formulation of relatively high molecular weight maltodextrin endowed with inclusion capacity and relevant charring can also be investigated in view of their fire retardance application [77].…”
Section: Perspectivesmentioning
confidence: 99%
“…Due to the capacity of including some FR components of low molecular weight in their cavities, BCD and BCD derivatives reduce the release to the environment of these species, resulting in an increase fire retardance activity and in more environmental friendly behavior. Introduction in FR formulation of relatively high molecular weight maltodextrin endowed with inclusion capacity and relevant charring can also be investigated in view of their fire retardance application [77].…”
Section: Perspectivesmentioning
confidence: 99%
“…Importantly, no additional bands at 1850 cm −1 and 1780 cm −1 can be seen in the cured fibers. These bands are ascribed to the C = O stretching of pyromellitic moieties formed by the scission of the ester bridge inside the Poly-βCD [36,37]. Their absence confirms that the thermal treatment does not damage the structure of the polymer in the fibers.…”
Section: Resultsmentioning
confidence: 88%
“…The synthesis of both the samples leads to the formation of a solid block that can be ground before being purified in Soxhlet. In our previous works [ 28 , 29 ], it has been reported that from pyrolysis of powdered nanosponges it is possible to obtain microporous carbons with spherical morphology. In order to control the dimension and the formation of carbon sphere, the nanosponges were ground and sieved in four parts with different particle sizes: higher than 100 μm, between 100 and 71 μm, between 71 and 40 μm, and less than 40 μm.…”
Section: Resultsmentioning
confidence: 99%
“…The β-cyclodextrin nanosponge (βNS) and Linecaps nanosponge (LcNS) were prepared dissolving 11.35 g of anhydrous βCD or Lc and 17.45 g of pyromellitic dianhydride in 100 mL of DMSO containing 2.7 mL triethylamine (19.4 mmol) and were allowed to react at room temperature for 1 h, as described elsewhere [ 28 , 29 ]. Once the reaction is over, the solid obtained could be ground in a mortar and Soxhlet extracted with acetone for 24 h.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation